On the Cost of Shame Comment on "Nudging by Shaming, Shaming by Nudging" - Emma Tieffenbach (Kerman University of Medical Sciences, 2014)
In his editorial, Nir Eyal argues that a nudge can exploit our propensity to feel shame in order to steer us toward certain choices. We object that shame is a cost and therefore cannot figure in the apparatus of a nudge.